Effects of Transcutaneous Electrical Acupoint Stimulation on Stress Response during Intubation and Extubation in Patients Undergoing Video-Assisted Thoracoscopic Surgery: A Prospective, Randomized Controlled Trial. (30th September 2021) - Yu, Zhiyan; Zhang, Yuying; Zhang, Huan; Zhao, Xue; Wei, Hua; He, Shuangliang; Liu, Jianming; Liu, Tiejun
Abstract : Objective . The study aimed to evaluate the effect of transcutaneous electrical acupoint stimulation (TEAS) on the stress response during intubation and extubation in patients undergoing video-assisted thoracoscopic surgery (VATS). Methods . 122 patients undergoing VATS lobectomy were randomly divided into two groups: the TEAS group ( n  = 62) and the control group ( n  = 60). Patients in the TEAS group underwent electroacupuncture stimulation of bilateral Neiguan (PC6), Hegu (L14), Lieque (LU7), and Chize (LU5) acupoints from 30 min before anesthesia to the end of surgery. The patients in the control group did not undergo stimulation. The primary endpoints were the hemodynamic parameters and plasma concentrations of epinephrine, norepinephrine, and cortisol. The secondary endpoints were the consumption of remifentanil and propofol, Ramsay sedation score and arousal time, extubation quality score, and postoperative complications. Results . The hemodynamic variables and plasma concentrations of epinephrine, norepinephrine, and cortisol during intubation and extubation were lower in the TEAS group at T1, T3, and T4 compared with the control group. TEAS led to a reduction in the consumption of remifentanil (P < 0.01 ), as well as a reduction in the incidence of postoperative complications. The extubation quality score was lower (P < 0.01 ) while the Ramsay sedation score was higher (P < 0.01 ) in the TEAS group than in the control group. However, the arousal time and consumption of propofol were not significantly different between the two groups. Conclusion . TEAS can maintain hemodynamic stability, reduce the stress response during intubation and extubation, improve the quality of anesthesia recovery, and decrease the incidence of postoperative complications in patients undergoing VATS.